Evaluation of Interaction Ciprofloxacin- Ascorbic Acid against Escherichia coli Inducing Urinary Tract Infection in Rats - Yahya, Nibras Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Escherichia coli O157 urinary tract infections are quite widespread all over the world. Few clinical investigations have indicated that ascorbic acid supplementation shortens the duration and symptoms of urinary tract infections. The purpose of this study was to determine whether ascorbic acid was impacted by the antibiotic therapy indicated for urinary tract isolates of E. coli O157. Our study aimed to determine the efficacy of ciprofloxacin, ascorbic acid, or a combination of both in eliminating Escherichia coli O157 bacteria that had grown in the urethra of male Wistar albino rats. Following infection events, the animals exhibited significant increases in serum and urine biochemical markers linked to kidney damage. We infected the animals with Escherichia coli O157 and treated them with ciprofloxacin, ascorbic acid, and a combination of ciprofloxacin and ascorbic acid orally once daily for 7 days. Animals treated with the combination displayed a significant improvement and disappearance of clinical signs during the first days of treatment, as well as the return of serum urine creatinine and serum albumin concentrations to normal levels at the end of the treatment period. The histological analysis of the kidney section in the positive control group revealed multifocal tubules with necrotic findings, sloughed epithelium in dilated tubules, and widespread infiltration of different cell types. After three days of therapy, the combination group showed an intact histological structure, similar to the negative control group. However, it was determined that in vivo study against Escherichia coli O157 in the treatment of urinary tract infection, the combination of ascorbic acid and ciprofloxacin was more potent and safer than ascorbic acid and ciprofloxacin separately